Developing affordance model of smartphone user interface for older adults - Wong, Chui Yin (2019)
With a global increase in population ageing, Malaysia is expected to be an aged nation by 2035. Concurrent with the change in the demographic composition, smartphones have become ubiquitous mobile communication tools for a growing proportion of older adults in Malaysia. However, the older adults are generally perceived as technophobic. Smartphone user interface (UI) and some mobile apps are not designed to meet the needs and expectations of older adults. The gap in perception and intended use hinders older adults from fully utilizing the functions and services of a smartphone. Affordance is defined as ‘perception and possibilities of actions for users (older adults) while interacting with an object (smartphone UI).’ This study refers to Norman’s Execution/Evaluation Action Cycle (EEAC) model and Gaver’s Technology Affordance. This study aims to develop an affordance model on perception and action possibilities of smartphone UI for older adults. A conceptual framework and hypothetical model of the study were formulated. This research employs multiphase design mixed methods methodology. Phase 1 is a preliminary study using quantitative method (survey). This is followed by Phase 2 consisting of mobile-user interaction study using mixed methods which is ‘concurrent embedded design’ (questionnaire, observation, and interview). Results from Phase 1 indicate smartphone usage among the older adults and justification of task design for Phase 2. The sample size for Phase 2 study was 80 ‘young-old’ adults, from 60 to 74 years old. To validate the affordance model, merged data analysis strategies were performed for quantitative and qualitative data. The empirical study indicates that 11 out of 16 hypotheses are supported. It is concluded that the affordance model is supported by the empirical findings. The major contribution of this study is the development of an affordance model, which is considered novel and adds value to the body of knowledge for Human-Computer Interaction and Gerontechnology. Based on the findings, it is crucial to incorporate older adults’ needs and expectations to reduce affordance gap with the underlying affordance matrix.